The potential of olfaction loss to induce cognitive impairment and anxiety behavior in mice via the microbiota-gut-brain axis - Zhao, Xiangyu; Xue, Chao; Wang, Yiming; Liu, Xiwei; Li, Ran; Yi, Xianfeng (Frontiers in Microbiology, 2025)
IntroductionOlfactory dysfunction and cognition decline are frequently observed; however, very little is known about whether olfactory disorders trigger cognitive impairment.MethodsHere, we induced olfactory loss in mice and investigated whether and how olfactory loss induces cognitive impairment and anxiety behavior.ResultsOlfactory loss not only causes a significant decrease in food intake and body weight and an increase in O2 consumption but also induces cognitive impairment and anxiety behavior. Olfactory loss-induced alteration of the gut microbiota is associated with subsequent changes in cecal short-chain fatty acids and serum neurotransmitter levels. Hippocampus proteome and fecal microbial transplantation provide further support for the mechanisms by which olfactory loss triggers cognitive impairment and anxiety behavior via the microbiota-gut-brain axis.DiscussionOur study is expected to provide some evidence for olfactory dysfunction in triggering cognitive impairment through the microbiota-gut-brain axis.